A Systematic Review of the Association Between Muscular Fitness and Telomere Length Across the Adult Lifespan - Marques, Adilson; Peralta, Miguel; Marconcin, Priscila; Henriques-Neto, Duarte; Gouveia, Élvio Rúbio; Ferrari, Gerson; Martins, João; Sarmento, Hugo; Ihle, Andreas (Frontiers in Physiology, 2021)
This study aimed to systematically review the association between telomere length (TL) and muscular fitness. In October 2020, an articles search was applied to PubMed, Scopus, and Web of Science. Eligibility criteria included: cross-sectional, prospective, and experimental study design; outcomes included TL; results expressed the relationship between muscular fitness and TL; studies published in English, Portuguese, or Spanish. Nine studies were included in the review. Results from the four prospective studies are mixed. In one study, the changes in TL were associated with grip strength. Another study concluded that longer mid-life TL was associated with increased grip strength later in life. However, in the other two studies, the association between TL and sarcopenia was not strong. Nevertheless, longer TL was associated with a slower decline in grip strength in older people. From the four cross-sectional studies, three indicated that TL was associated with muscular fitness. On the other hand, in a study with powerlifters, TL remained within the range of values found in subjects with no history of regular strength training, supporting the notion that muscular fitness was not associated with TL. The cross-sectional and prospective studies showed that the relationship between TL and muscular fitness is not conclusive. It seems that there is a positive association between TL and muscular fitness in middle-aged and older adults. However, among younger adults, this relationship was not observed.